IMM: SEBUAH PERGULATAN PEMIKIRAN DAN PRAKTIK ORGANISASI DALAM ISU KONTEMPORER - Dartim Dartim (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
The Muhammadiyah Student Association or IMM is a representation of the Muhammadiyah student movement engaged in the realm of science, religion and humanity. All three are very attached as representatives of the Islamic student movement. Moreover, structurally it has a very close relationship with the Muhammadiyah organization. This article will try to examine empirically and rationally the IMM movement in responding to contemporary thoughts and issues, especially those related to issues of education and cadre, religion and humanity, as this movement was originally initiated.